Alterações comportamentais, bioquímicas e moleculares em camundongos C57BL/6 machos após recuperação de malária cerebral - Souza, Thaíze Lopes de (2017)
Malaria, a parasitic disease, can be caused by different species of Plasmodium protozoan and it is transmitted by the bite of female Anopheles mosquitoes. Plasmodium falciparum is responsible for the most severe complication of malaria infection, cerebral malaria (CM), as well as, even after successful antimalarial therapy, is related to high mortality and enduring cognitive impairment, which are not completely elucidated. The present study, through an experimental model of cerebral malaria obtained through the inoculation of Plasmodium berghei ANKA in C57BL/6 male mice, aimed to determine the influence of this severe condition on behavior, biochemical parameters and gabaergic neurotransmission of these animals. We hypothesized that cerebral malaria is capable to induce changes in the central nervous system, which may have the mechanism of action elucidated through the induction of the experimental model, thus making it possible to clarify the data already reported in the clinical literature. When compared to control animals, we observed that the infected mice showed increased phosphorylation of Na+,K+-ATPase at Ser943, determined by Western Blot technique, as well as decreased activity of the enzyme isoforms containing α2/α3 subunits in cerebral cortex samples. In addition, in this same tissue, through [3H]-Flunitrazepam assay, a reduction in binding capacity of GABAA receptors was observed in animals recovered from cerebral malaria, whereas in samples obtained from the hippocampus, by Dot Blot technique, it was possible to find an increase in the expression of carbonylated proteins. Although we did not find macroscopic histological changes, behavioral tests showed that the expected natural behavior for C57BL/6 mice was altered after infection and recovery, since it was observed a decrease in the nest building rate and an increase in the number of marbles buried when compared to the control group. Therefore, the data presented in this study demonstrate that behavioral and neurochemical changes persist even after parasite eradication and remission of CM, being in agreement with clinical findings and also may be related to the increased susceptibility to seizures demonstrated in previous studies. Although more studies are needed, biochemical markers presented in this study may become a target for the development of new therapeutic strategies for CM.